Factors associated with hospitalizations and deaths of pregnant women from Paraná due to COVID-19: a cross-sectional study - Larissa Silva Bergantini; Sueli Mutsumi Tsukuda Ichisato; Maria Aparecida Salci; Marcela Maria Birolim; Márcia Lorena Alves dos Santos; Carla Franciele Höring; Roberta Rossa; Luiz Augusto Facchini (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To analyze the factors associated with hospitalization in the ward and intensive care unit (ICU), and with death from COVID-19 in pregnant women with confirmed cases. Methods: Observational, cross-sectional study, carried out with data from pregnant women with a confirmed case of COVID-19 from the Influenza Epidemiological Surveillance Information System and the Paraná's state COVID-19 notification system. The association between the independent and dependent variables (hospitalization in the ward and ICU, and death) was investigated using the Poisson regression model with robust variance. Results: 4,719 pregnant women comprised the study population. 9.6 and 5.1% were hospitalized in wards and ICU, respectively. 1.9% died. There was an association between advanced maternal age and hospitalization in wards (PR=1.36; 95%CI 1.10-1.62) and ICU (PR=2.25; 95%CI 1.78-2.71), and death (PR=3.22; 95%CI 2.30-4.15). An association was found between the third trimester and hospitalization in wards (PR=5.06; 95%CI 2.82-7.30) and ICU (PR=6.03; 95%CI 3.67-8.39) and death (PR=13.56; 95%CI 2.90-24.23). The second trimester was associated with ICU admission (PR=2.67; 95%CI 1.36-3.99). Pregnant women with cardiovascular disease had a higher frequency of hospitalization in wards (PR=2.24; 95%CI 1.43-3.05) and ICU (PR=2.66; 95%CI 1.46-3.87). Obesity was associated with ICU admission (PR=3.79; 95%CI 2.71-4.86) and death (PR=5.62; 95%CI 2.41-8.83). Conclusions: Advanced maternal age, the end of the gestational period and comorbidities were associated with severe COVID-19.